Teknologi Komunikasi Informasi dan Dekonstruksi Tren Pariwisata - Zakaria Lantang Sukirno; Edoardo Irfan (Diploma Travel Business, Faculty of Social and Political Science, Jember University, 2019)
Abstract ICT progress and dynamics has been changing human behavior and life. Thus, tourism industry has changed drastically because of the new media development. The changes in organizational order or structure, society, trend, and culture based on technology development become the signifier of postmodern era. ICT is responsible for the drastic change of tourist consumer behavior, tourist service companies, tourism marketing, and tourism business. That’s called as deconstruction. Tourism business must be sensitive to the consumer behavior and consumer culture deconstruction in this digital era that occurs in the tourism trend by following the ICT usage trend. Tourism entrepreneurs must deconstruct their mindset from competition to collaboration.Keywords : ICT, postmodern, deconstruction, tourism, apps, startup